Environmental Performance Ratings, Carbon Disclosure, and Firm Value: Evidence From Indonesia - Salim, Qolbin; Prasojo, Prasojo (Jurnal Dinamika Ekonomi Pembangunan, 2025)
This study examines the association between environmental performance ratings, carbon emission disclosure, and firm value in Indonesia’s energy and industrial sectors. The sample comprises firms listed on the Indonesia Stock Exchange and covered by the PROPER program during 2019–2023, yielding 160 firm-year observations from 32 firms. Firm value is proxied by Tobin’s Q. Environmental performance is measured using the Ministry of Environment and Forestry’s PROPER rating, while carbon emission disclosure is constructed based on a checklist derived from the Carbon Disclosure Project (CDP). Panel regression analysis controls profitability (ROE), sales growth, leverage (DER), and firm size (SIZE). The results indicate that environmental performance ratings are not significantly associated with firm value, whereas carbon emission disclosure exhibits a positive and statistically significant association. Among the control variables, only profitability shows a significant relationship with firm value. These findings suggest that, in this context, investors place greater weight on transparent and decision-useful carbon-related disclosure than on aggregate environmental performance ratings. The study provides evidence from an emerging market setting and offers implications for regulators and firms regarding the relative valuation relevance of disclosure quality and performance ratings.